METHODOLOGY OF CREATING VIRTUAL LABORATORIES IN "LABVIEW" SOFTWARE - Zoirov Sanjaridin Xolmuminovich; Ikromov Amirhon; Qarshiboyev Shavkat Esirgapovich; Norqulova Matluba Mamatmurod qizi; Xoshimov Temur Faxriddin o‘g‘li, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Methods of virtual creation of physical processes and experiments on the computer using computer technologies in the fields of physics and electronics education are considered. We will look at the possibilities of using the technology of creating virtual laboratories in the "LabVIEW" program in the educational process.